Dietary Macronutrient Composition and Gestational Weight Gain Among Pregnant Women During the Second Trimester (P08-018-19). (24th October 2019) - Wyst, Kiley Vander; Buman, Matthew; Shaibi, Gabriel; Petrov, Megan; Reifsnider, Elizabeth; Whisner, Corrie
Abstract: Objectives: Higher energy intake has been associated with increased gestational weight gain (GWG). However, the effects that individual macronutrients have on GWG remain unclear. We examined the putative mediating effect of macronutrient composition on GWG after an intervention aimed to track prenatal energy needs. Methods: In this controlled trial, pregnant women aged >18 yr old (X = 29.8 ± 4.9 yr) with a gestational age (GA) <17 wk were randomized to Breezing™ (N = 16) or control (N = 12) groups for 13 wk. The Breezing™ group used a real-time metabolism tracker to obtain their resting energy expenditure. Anthropometrics and diet data were collected every 2 weeks. Overall rate of GWG was calculated as total weight gain divided by total study weeks. Early (GA wk 14–21), late (GA wk 21–28), and overall (GA wk 14–28) changes in macronutrients and GWG were calculated. Simple mediation models were constructed using SPSS PROCESS macro Model 4 using a bootstrap estimation approach with 5000 samples. Results: There was no difference in total (8.13 vs. 7.17 kg, P  = 0.37) or rate (0.58 vs. 0.53 kg/wk, P  = 0.57) of GWG among Breezing or control groups. Breezing women gained significantly more [F(1, 24) = 5.29, P  = 0.03] and had a higher rate of GWG [F(1, 24) = 4.48, P  = 0.05] in the latter half of the 2nd trimester. Women gained more than the recommended GWG based on study start BMI. Early, late, and overall total energy (kcal/d), fat (g/d), and carbohydrate (g/d) intakes were not different between groups. Late changes in protein significantly differed [–15.62 vs. 24.86 g/d, t(26) = –2.92, P  < 0.01] among Breezing and control groups, which explained 25% of the variance. A difference in overall change in protein intake between the Breezing and control groups (–0.94 vs. 21.77 g/d) approached significance [t(26) = 1.77, P  = 0.08]. There was no mediation effect of early, late, or overall changes in macronutrients on GWG. Overall, a trend emerged, that for each one gram increase in protein, there was a decrease in total GWG of 0.02 kg [β = –0.02, t(26) = –1.75, P  = 0.09] in the late half of the 2nd trimester. Conclusions: Macronutrient composition did not mediate the intervention effect probably due to the study being underpowered to detect mediation. However, use of the Breezing device significantly predicted late changes in protein intake, suggesting that variability in maternal protein intake may influence GWG. Funding Sources: Project HoneyBee, Arizona State University.